2020
DOI: 10.36688/imej.3.45-54
|View full text |Cite
|
Sign up to set email alerts
|

effects of surge motion on floating horizontal axis tidal turbines

Abstract: Wave induced motions due to actual sea state conditions will impact the performance of floating horizontal axis tidal turbine systems. This paper presents the results from numerical simulations of a 3-bladed horizontal axis tidal turbine oscillating in surge motion in a moving reference frame. The optimum tip-speed ratio, λ = 4.4 and k-ω SST turbulence model were used in the present study. The Navier-Stokes equation was modified by adding an inertial term to the equation and the Dirichlet boundary condition wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The bullet points show mean quantities, while bars The thrust plots show that mean values are not significantly influenced by waves nor by platform motions. This is in agreement with the results presented by, e.g., Galloway et al (2014), de Jesus Henriques et al (2014), and Guo et al (2018a, for cases of rotors operating under the influence of surface waves, and by Osman and Willden (2020) and Osman et al (2019) for rotors under prescribed motions. The load fluctuation magnitude, however, varies between cases as a function of wave period.…”
Section: Rotor Loads and Performancesupporting
confidence: 93%
See 1 more Smart Citation
“…The bullet points show mean quantities, while bars The thrust plots show that mean values are not significantly influenced by waves nor by platform motions. This is in agreement with the results presented by, e.g., Galloway et al (2014), de Jesus Henriques et al (2014), and Guo et al (2018a, for cases of rotors operating under the influence of surface waves, and by Osman and Willden (2020) and Osman et al (2019) for rotors under prescribed motions. The load fluctuation magnitude, however, varies between cases as a function of wave period.…”
Section: Rotor Loads and Performancesupporting
confidence: 93%
“…The motion of a rotor in some of these degrees of freedom, decoupled from waves, has been studied through the simulation of rotors under prescribed motions. Osman et al (2019), Osman and Willden (2020), for example, studied a tidal rotor under prescribed surge and pendular motions, respectively, using Reynolds-Averaged Navier Stokes (RANS) CFD simulations. Similar to the cases above of rotors under the influence of surface waves, the studies on prescribed motions demonstrated that mean loads are largely unaffected as long as no significant flow separation is observed on the blades.…”
Section: Introductionmentioning
confidence: 99%
“…The axial damping coefficient of the turbine was derived by using the least squares method and was found to have no significant correlation with the amplitude and frequency of the surge motion. Osman [13] obtained similar results in their study. Jiang [14] studied the load variation of a vertical-axis tidal current turbine under the coupling effect of roll and yaw.…”
Section: Introductionsupporting
confidence: 70%
“…Surge oscillations result in velocity perturbations that are uniform across the rotor (Zhang et al 2015), whereas platform pitching motions create a spatially varying velocity perturbation. Turbine blades may temporarily stall under large platform motions, which tend to reduce the mean thrust and power compared to the nonoscillating case and significantly increase fatigue loads (bin Osman et al 2019). The added mass of turbines oscillating in surge has been found to be modest (Whelan et al 2009, bin Osman et al 2019.…”
Section: Unsteady Loadingmentioning
confidence: 99%
“…Turbine blades may temporarily stall under large platform motions, which tend to reduce the mean thrust and power compared to the nonoscillating case and significantly increase fatigue loads (bin Osman et al 2019). The added mass of turbines oscillating in surge has been found to be modest (Whelan et al 2009, bin Osman et al 2019.…”
Section: Unsteady Loadingmentioning
confidence: 99%